AN AUDIT OF THE MANAGEMENT OF ACUTE PAIN IN CHILDREN. Issue 9 (17th August 2016) - Sidhu, Junndeep; Tickner, Neil
Abstract : Aim: To evaluate clinical management of acute pain with respect to pain assessment, scoring and timing of analgesia and whether appropriate supportive medicines were prescribed alongside strong opiates. A previous pain audit found dosing of analgesia was appropriate but did not assess clinical management against pain scores. Our paediatric guideline does not currently stipulate guidance on appropriate time frames to administer analgesia and re-assess pain. Standards were developed with a multidisciplinary team to audit against. Methods: Data were collected over two weeks on paediatric wards excluding intensive care and day surgery. Inclusion criteria: Pain score of ≥1 during admission, or clear documentation of pain prior to ward admission, and analgesia prescribed for the indication of pain relief. Pain assessment was audited based on recorded pain scores on observation charts. Analgesia prescribed and administered was audited from drug charts. Audit standards: (1) Following a pain score of ≥1 (out of 3), subsequent dosing and assessment of pain scores must be achieved in 80% of patients as follows: (a) Severe/worst pain (score 3): Should receive appropriate analgesia within 20 minutes of assessment and pain re-evaluated within 5-minute intervals for intravenous and intranasal route or within 30 minutes of receiving oral analgesia. (b) Mild/moderate pain (score 1–2): Should receive appropriate analgesia within 30 minutes of assessment and pain re-evaluated within 60 minutes of receiving analgesia. (2) 80% of patients prescribed regular analgesia should have their pain score assessed at least 4-hourly. (3) 90% of patients prescribed strong opioid analgesia should be co-prescribed naloxone prn for respiratory depression and pruritus/urinary retention. Results: Twenty-five patients were audited. In total there were 59 severe pain scores and 92 mild/moderate. Observation charts allowed for documentation of pain scores at 15-minute intervals but only hourly recordings were observed throughout the audit period. 58% (34/59) and 30% (28/92) of pain scores indicating severe or mild/moderate pain respectively received analgesia in the same hour the pain score was recorded. In total there were 71 analgesia administrations for severe pain and 92 for mild/moderate pain. 52% (37/71) and 34% (31/92) of analgesia administrations after severe or mild/moderate pain scores respectively had a pain score re-assessed within 60 minutes. Eighteen patients were prescribed regular analgesia of whom 15 (83%) had pain assessed a minimum of every 4 hrs. Eleven patients were prescribed strong opioid analgesia, 45% of whom were not prescribed any naloxone, 27% had naloxone fully prescribed (pruritus and respiratory depression), and 27% had naloxone prescribed for respiratory depression alone. Conclusion: Despite lack of guidance around timing of pain assessment and administration of drugs, pain scores were being recorded regularly and acted upon, although not within a structured time frame. Observation charts allowed for assessment of pain scores at 15-minute intervals but only 'on the hour' documentation were observed. Specific guidance around timing of analgesia administration and assessment will be introduced to the revised guideline with medical and nurse training sessions to standardise practice and improve management of pain, in addition to safe prescribing of opiates.